(untitled) (Scientific journal of the Fergana State University, 2024)
The future of every social system, human perspective, people’s life and standard of living are directly related to the development of science and culture. In the past, Eastern thinkers, based on their life experiences, left a rich historical experience of education and personal development, which is the foundation of our spirituality. The article talks about the specific features of educating students in the national spirit on the basis of folk pedagogy, the unique pedagogical ideas of individual upbringing, education and development in folk pedagogy.